The Influence of the Problem Based Learning Model on Students' Mathematical Problem Solving Ability in Mathematical Induction Material - Syara, Lili; Pasaribu, Laili Habibah; Harahap, Amin (Graduate School of Universitas Negeri Malang, 2024)
This research was motivated by the low mathematical problem solving abilities of students at Muhammdiyah 10 Rantauprapat Private High School. This is because the model used by teachers is still not varied, where teachers only explain and teachers only take notes without actively involving students in learning. In this case the researcher uses the Problem Based Learning (PBL) model. The aim of this research is to determine the effect of using the Problem Based Learning (PBL) learning model on the mathematical problem solving abilities of class The population in this study were all students in class The average pretest result is 38.00 and the average posttest result is 85.33, meaning the average posttest score is higher than the pretest score. From the hypothesis test, it was obtained that t = 5.556 and t table = 2.048. So if we consult the t table with a significance level of 0.01, the results show that 5.556 > 2.048. This means that t count is greater than t table. So it can be concluded that the Problem Based Learning (PBL) learning model has a very significant influence on the mathematical problem solving abilities of students in class This is strengthened because the Problem Based Learning (PBL) model has advantages and goals that are able to encourage students to learn more effectively because they focus on problem solving and students are able to develop themselves.